THE INFLUENCE OF pH ON INTERACTION OF CuTOEPyP4 WITH DNA - Dalyan, Ye. B.; Vardanyan, I. V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
The interaction of Cu(II)-meso-tetra-(4N-hydroxyethylpyridyl)porphyrin (CuTOEPyP4) with DNA at different pH was studied by methods of spectrophotometry and circular dichroism. It was shown that these porphyrins bind to DNA preferably via intercalation. The calculations show that the constant of binding of CuTOEPyP4 with DNA strongly depend upon the pH.